Brazil: from Eliticized- to Mass-Based Financialization. - Lena Lavinas; Eliane Araújo; Miguel Bruno (Revue de la Régulation)
While research on financialization, considered the latest stage of the development of capitalism, initially focused on industrialized countries, it has now expanded to include emerging markets. This article provides new insights into the current Brazilian case, while arguing also that Brazil was already grappling with a premature, eliticized process of financialization in the 1980s, however embryonic. From the 2000s on, there came a new wave of financialization. This time, however, it was mass-based, using social policy as collateral. The article first establishes a timeline for and taxonomy of how financialization has been deployed in Brazil. It then examines how policies aimed at promoting social inclusion have been diverted to that end. Finally, it presents regression analyses demonstrating a negative correlation between financialization and the provision of public goods and services, which has become increasingly privatized. It also finds a positive relationship between financialization and income and cash transfers, the latter serving as collateral for the former.